2018
DOI: 10.1002/fam.2650
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between magnesium hydroxide and microencapsulated red phosphorus in flame‐retarded high‐impact polystyrene composite

Abstract: Summary High‐impact polystyrene (HIPS) flame retarded by magnesium hydroxide (MH) alone or in combination with microencapsulated red phosphorus (MRP) was prepared by melt compounding, and the interaction between MH and MRP was investigated by limiting oxygen index, UL‐94 vertical burning test, cone calorimeter test, X‐ray diffraction, thermal analysis, and scanning electron microscopy. Obvious synergism between MH and MRP on the flame retardancy of HIPS is found. The introduction of a small amount of MRP can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The reason may be that RP reacted with water vaper at this temperature range and generated H 3 PO 4 , which further catalyzed the char-forming process of the decomposing EP thus suppressed its degradation rate. 16 This phenomenon was consistent with the increased char residuals of FR-EP shown in Fig. 10(a) , and the highest char residual weight ratio and lowest weight loss rate at T max of EP/RP@PDA/MA7.0 indicated that RP@PDA/MA can improve the thermal stability of EP efficiently.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The reason may be that RP reacted with water vaper at this temperature range and generated H 3 PO 4 , which further catalyzed the char-forming process of the decomposing EP thus suppressed its degradation rate. 16 This phenomenon was consistent with the increased char residuals of FR-EP shown in Fig. 10(a) , and the highest char residual weight ratio and lowest weight loss rate at T max of EP/RP@PDA/MA7.0 indicated that RP@PDA/MA can improve the thermal stability of EP efficiently.…”
Section: Resultssupporting
confidence: 85%
“…To overcome these shortcomings, RP is generally coated by an organic shell structure to fabricate microencapsulated RP (MRP) before it can be used as an applicable ame retardant. [16][17][18] Additionally, when specic synergistic materials are applied as the shell structures, MRP can constitute an integrated IFR system, which is supposed to further improve the ame retardance of pristine RP.…”
Section: Introductionmentioning
confidence: 99%
“…The heat released by the decomposition of the matrix accelerates the oxidation of RPHNs and decomposes into high-activity phosphorus species (for example, phosphoric acid), 35 followed by conversion to polyphosphate, which promotes the dehydration of oxygen-containing molecular chains and further accelerates the formation of a char layer. 36 Subsequently, for the matrix, the second rapid decomposition occurs at 440−535 °C, which is mainly attributed to the condensation of the formed metaphosphoric acid at high temperature to form polyphosphoric acid with better thermal stability. 35 With the excellent char-forming performance of RPHNs, the residual weight of the matrix is up to 27.7% at 800 °C.…”
Section: Thermal and Flame-retardantmentioning
confidence: 99%
“…However, HIPS are flammable, thus underlining the importance of flame retardant treatments. The flame retardants used in HIPS are mainly phosphorus flame retardants, [23][24][25][26][27][28][29][30] metal hydroxides 23,24,31,32 and various brominated flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been reported that there is good synergism between magnesium hydroxide and microencapsulated red phosphorus in HIPS. 23 Although there are many reported flame retardants that can be used in HIPS, the primarily used flame retardants are brominated flame retardants, as they have better comprehensive performance. The most common brominated flame retardants are decabromodiphenyl ether (decaBDE), 36,37 tetrabromobisphenol A (TBBA) and its derivatives, 37 decabromodiphenyl ethane (DBDPE), 36,37 etc.…”
Section: Introductionmentioning
confidence: 99%